2021
DOI: 10.3390/su13158613
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Road Traffic Crashes among Novice Female Drivers in Saudi Arabia

Abstract: Background: Recently (in 2018), females were legally allowed to drive and use automobiles in Saudi Arabia (SA) for the first time. This study investigated and analyzed the general fear of driving (GFDS), perceived self-confidence (PSCR), socio-economic variables, demographic distribution, and self-reported RTCs in novice female drivers from SA. Methods: The work was based on survey responses from 9608 participants from the first generation of female drivers from SA. Factor analysis was used to extract GFDS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In 2018, Saudi Arabia allowed female citizens to have a license, which increased the number of young drivers in the country. Car ownership and RTCs are also expected to increase [49]. Hence, it is crucial to proactively mitigate RTCs involving young road users in Saudi Arabia.…”
Section: Yang Zeyin Et Al [39] 18-25 Years Chinamentioning
confidence: 99%
“…In 2018, Saudi Arabia allowed female citizens to have a license, which increased the number of young drivers in the country. Car ownership and RTCs are also expected to increase [49]. Hence, it is crucial to proactively mitigate RTCs involving young road users in Saudi Arabia.…”
Section: Yang Zeyin Et Al [39] 18-25 Years Chinamentioning
confidence: 99%
“…"Assessing the road traffic crashes among novice female drivers in Saudi Arabia" [14] To In articles [7,12,13], the importance of advanced real-time driver information systems is emphasized. The authors of [7] provided the results of a field experiment that confirms the advances of the presented application: increased driver attention and pursuit of safe driving.…”
Section: Title Objective Type Of Analyzed Data Conclusionmentioning
confidence: 99%
“…The authors of [14][15][16] examine the factors of driver behavior that influence traffic accidents in different cultures. Based on the three studies, it can be concluded that the factors that affect traffic safety vary widely among different cultures.…”
Section: Title Objective Type Of Analyzed Data Conclusionmentioning
confidence: 99%
“…Al-Garawi et al [18] recently assessed traffic crashes among novice female drivers in the KSA. Their study concluded that single, divorced/widowed, employed, and highincome female novice drivers were at a higher danger of being involved in road-traffic crashes, whether they hired personal trainers or not.…”
Section: Introductionmentioning
confidence: 99%